Building resilience through dynamic monitoring of shocks and enhanced access to near-real-time information using citizen science and crowdsourcing techniques: A report of a national stakeholder engagement workshop in Ethiopia - Shikuku, Kelvin Mashisia; Lepariyo, Watson; Gobu, Wako; Godana, Nura; Baraza, Meshack; Ochenje, Ibrahim; Banerjee, Rupsha R. (International Livestock Research Institute, 2025)
The International Livestock Research Institute, with funding support from the Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) programme, has established and monitored sentinel sites in five counties in Kenya and in the Borena, Afder, and East Hararghe zones in Ethiopia. The work is implemented under the Drought Index-insurance for Resilience in the Sahel and Horn of Africa (DIRISHA) project. Through the DIRISHA project, transect sites have been constructed, markets monitored, and households surveyed by “contributors” recruited using a participatory approach that includes community members and local leaders. Crowdsourced data are gathered using the KAZNET smartphone application. Dissemination of near-real-time information is achieved by combining social learning and digital innovations. This report summarizes insights generated during a participatory multi-stakeholder workshop in Ethiopia aimed at sharing DIRISHA project learnings and exploring prospects for incorporating KAZNET into climate risk management and food system transformation initiatives in Ethiopia.